2011
DOI: 10.1139/v11-025
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-31 and vanadium-51 solid-state nuclear magnetic resonance spectroscopy of β-vanadyl phosphate — Effects of homo- and heteronuclear spin-spin, electrostatic, and paramagnetic interactions

Abstract: Field-dependent 31 P solid-state NMR studies demonstrate that the line shape in spectra of b-VOPO4 depends on 51 V-31 P direct and indirect spin-spin interactions (M 2 ( 51 V, 31 P) = 101(23) × 10 6 rad 2 s -2 , 2 J iso ( 51 V, 31 P) = 48(5) Hz) and, to a lesser extent, on 31 P chemical shift anisotropy (d iso = -10.4(2), U = d 11 -d 33 = 22(2) ppm) and 31 P-31 P interactions (M 2 ( 31 P, 31 P) = 6.7(1) × 10 6 rad 2 s -2 ). In contrast, homonuclear dipolar interactions play an important role for the field and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 119 publications
(117 reference statements)
4
3
0
Order By: Relevance
“…A related earlier work is due to Eichele and Grimmer, who studied the longitudinal (T 1 ) relaxation of 31 P in a sample containing paramagnetic impurities, which provides an indirect measure of the homonuclear spin diffusion efficiency [16]. Similarly to our study, they observed a decrease of T 1 at slow (1-2 kHz) MAS, see Fig.…”
Section: Discussion Of Literature Datasupporting
confidence: 85%
See 3 more Smart Citations
“…A related earlier work is due to Eichele and Grimmer, who studied the longitudinal (T 1 ) relaxation of 31 P in a sample containing paramagnetic impurities, which provides an indirect measure of the homonuclear spin diffusion efficiency [16]. Similarly to our study, they observed a decrease of T 1 at slow (1-2 kHz) MAS, see Fig.…”
Section: Discussion Of Literature Datasupporting
confidence: 85%
“…Based upon our previous work [15], we here studied local spin diffusion rates under MAS, and observed increased spin diffusion coefficients at low (<10 kHz) spinning rates as compared to static conditions, with a maximum spin diffusion efficiency around 2-3 kHz MAS. The effect is supported by previous T 1 relaxation data on a sample experiencing spin diffusion driven T 1 [16]. The fact that slow MAS enhances spin diffusion may be of particular interest for certain of the above-mentioned applications.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In paramagnetic compounds, the hyperfine interaction is included in the internal nuclear-spin interactions. , Fast paramagnetic relaxation can cause broadening of the NMR spectra, although in some cases it is advisedly used for speeding up NMR measurement. , The hyperfine coupling also affects the spectra as a change of line shape by the anisotropic component and as a whole shift by the isotropic component. Although numerous structural studies of paramagnetic materials have been conducted by solid-state NMR with 7 Li and other HIQN such as 51 V, 59 Co, 95 Mo, 137 Ba, and 139 La, the spectra have not been simulated by considering both isotropic and anisotropic effects from the second-order quadrupole, chemical shift and hyperfine interactions as far as we know. The present work performing numerical simulation of the 95 Mo spectra combined with DFT calculation for the paramagnetic crystal would be a challenging attempt.…”
Section: Introductionmentioning
confidence: 99%